1973
DOI: 10.1021/ja00785a005
|View full text |Cite
|
Sign up to set email alerts
|

Photochemistry of silicon compounds. IV. Mercury photosensitization of disilane

Abstract: The room-temperature mercury 6(1 23Pi) photosensitization of disilane produces H2, SiH4, Si3H8, Si4Hio, and a solid deposit. From detailed kinetic studies using deuterium-labeling techniques and scavengers such as NO and C2H4 it has been established that the sole primary step is Hg 6(3 4

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

1977
1977
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(17 citation statements)
references
References 3 publications
2
15
0
Order By: Relevance
“…Ethene 31,34,36-38 and propene 31,34 are known to be good free radical scavengers. This fact is in agreement with work done by Pollock et al 37 in which they found that the trapping reaction of silyl radical (ÁSiH 3 ) by ethene is two to three orders of magnitude faster than its addition to alkyl radicals and also more rapid than the addition reaction of the trimethylsilyl radical to ethene. Among these radicals, some are methylsubstituted silyl radicals [e.g., (CH 3 ) 3 SiÁ, (CH 3 ) 2 HSiÁ], others are (silyl-substituted) alkyl radicals] e.g., (CH 3 ) 2 SiHCH 2 Á, ÁCH 3 ].…”
Section: Radical Recombination Reactionssupporting
confidence: 93%
“…Ethene 31,34,36-38 and propene 31,34 are known to be good free radical scavengers. This fact is in agreement with work done by Pollock et al 37 in which they found that the trapping reaction of silyl radical (ÁSiH 3 ) by ethene is two to three orders of magnitude faster than its addition to alkyl radicals and also more rapid than the addition reaction of the trimethylsilyl radical to ethene. Among these radicals, some are methylsubstituted silyl radicals [e.g., (CH 3 ) 3 SiÁ, (CH 3 ) 2 HSiÁ], others are (silyl-substituted) alkyl radicals] e.g., (CH 3 ) 2 SiHCH 2 Á, ÁCH 3 ].…”
Section: Radical Recombination Reactionssupporting
confidence: 93%
“…In this case, a simple approach consists to balance the creation and loss rate of AB* in order to derive the effective rate constants kl,eff for the total reaction and k~,~f f and ks,eff for the production of C + D or AB, 1: BECERRA et al [204]; m: the association excited product Si3HT should easily dissociate along the proposed exothermic channel and little pressure dependence is expected, as opposed to the reaction of SiH with SiH4 producing Si2H: for which the dissociation into SizH~fHz is nearly thermoneutral; n: POLLOCK et al [205]; 0: ITABASHI et al [206]; p: LOH et al [207]; q: KosHI et al [208] +SiHz where Po and To are standard pressure and temperature. Such expressions can be used to fit experimental data obtained at different pressures.…”
Section: A + B -A B * -C + D mentioning
confidence: 99%
“…Several studies have claimed that ethene efficiently traps methylsilyl radicals. [28][29][30][31] Neudorfl and Strausz 29,30 studied the pyrolysis of MMS and DMS in the presence of ethene as a radical scavenger. In the presence of ethene, they found that the products generated from the free radical chain reaction are completely suppressed, while the ones evolved from the reaction of silene−silylene intermediates are still detected but with reduced yield.…”
Section: Intensity (Au)mentioning
confidence: 99%
“…This observation was obtained by several other studies when using ethene as a free-radical scavenger. 24,25,28,31 Therefore, ethene can react with both silyl radicals and silylene species. The trapping adduct formed from the reaction of ethene with the parent silyl (·SiH 3 ) radical and silylene (:SiH 2 ) species is ethylsilane and silacyclopropane, respectively.…”
Section: Intensity (Au)mentioning
confidence: 99%